KEBIJAKAN GERAKAN LITERASI SEKOLAH (Konsep dan Implementasi) - Zaina Al Fath; Ayu Sholina; Fitratul Isma; Deby Indriani Rahmawan (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
This article aims to describe the implementation of the literacy school program (LSP) as an educational policy that seeks literacy skills in mathematics, science, reading and writing of students. The literacy school program (LSP) is the result of educational innovation in the field of strategy. The literacy school program emphasis on literacy activities that include thinking skills using sources of knowledge in print, visual, digital, and auditory forms. This article uses a library research with literature and internet. The implementation of literacy school program (LSP) in primary school is applied as regulation of Ministry of Education and Culture number 23 of 2015 concerning the cultivation of character strengthens the efforts to establish the culture of literacy.